La politique de communication de la Commission a-t-elle créé un espace public européen interculturel ? - Éric Dacheux (Communiquer)
The European Union is an interesting political space for analyzing the points of contact between research on international communication and research on intercultural communication. Indeed, the European Union (EU) is obviously with 28 countries (soon 27) a space where unfolds an international multilingual communication. It is also a political institution that seeks to create an intercultural public sphere to legitimize a “united in diversity” political structure (EU motto). Is this institutional goal achieved? Can the communication policy implemented by the EU executive (the European Commission) for 500 million Europeans help to create a space for mediation and engagement that is common as well as respectful of cultural diversity? The purpose of this article is to answer this question.